2023
DOI: 10.3390/ijms24076432
|View full text |Cite
|
Sign up to set email alerts
|

Dental Material Selection for the Additive Manufacturing of Removable Complete Dentures (RCD)

Abstract: This research addresses the development of a formalized approach to dental material selection (DMS) in manufacturing removable complete dentures (RDC). Three types of commercially available polymethyl methacrylate (PMMA) grades, processed by an identical Digital Light Processing (DLP) 3D printer, were compared. In this way, a combination of mechanical, tribological, technological, microbiological, and economic factors was assessed. The material indices were calculated to compare dental materials for a set of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Thermal transmittance, 8. Thermal wave shift Fuzzy BWM Grachev et al 45 Dental material selection in manufacturing removable dentures 1. Mechanical properties, 2.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal transmittance, 8. Thermal wave shift Fuzzy BWM Grachev et al 45 Dental material selection in manufacturing removable dentures 1. Mechanical properties, 2.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The materials were ranked using AHP-VIKOR, AHP-TOPSIS, AHP-MOORA, AHP-ELECTRE, and AHP-PROMTHEE methods. Grachev et al 45 developed a formalized method for selecting dental materials in the production of removable dentures. Their approach combined AHP-Extended VIKOR method and involved analyzing interval quantitative estimations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many published papers have been devoted to a comparison and evaluation of their capabilities [19][20][21]. Earlier, in an article by the authors [5], it was shown that it is sufficient to use the combined AHP-VIKOR method for solving the problems of the selection of dental materials. In this study, an algorithm was developed for ranking the mechanical properties.…”
Section: Development Of the Quality Assessment Criteria And Ranking O...mentioning
confidence: 99%
“…is the P(∆l) curve length on the ∆l ∈ [∆l 1 , ∆l N ] segment. Table A1 (Appendix A) presents the calculated values of the non-linearity coefficients according to the above expressions (1)- (5).…”
Section: Development Of the Quality Assessment Criteria And Ranking O...mentioning
confidence: 99%
See 1 more Smart Citation